Delay in civil proceedings: problems and solutions / Farah Shuhadah Razali ...[et al.] - Razali, Farah Shuhadah; Abu Zahar, Khaidhirah; Sanusi, Nurman Rummel; Mansor, Nurul Huda (2006)
As one of the three main branches of the government, the judiciary plays a pivotal role in maintaining the balance of power between the organs of the government as well as being the medium through which justice is sought and served. The importance of maintaining the integrity of the body and faith of the people is profound, as doubt and lack of assurance in any way towards the judiciary would undoubtedly mar the system thus leading to a bigger conflict. Many a times, reports on the causes of delay is attributed to the lawyers and judges. However, this is not entirely accurate as there are also other causes that contribute to the backlog of cases. This research is conducted in our pursuit to discover the reasons behind the delay in civil proceedings (particularly in the High Courts) and the probable solutions by looking at the practices of countries such as Singapore and United Kingdom. By conducting this research, new steps or procedures can be proposed to rectify the current system of justice so as to accommodate to the changes surrounding us. It is hoped that those who read it would have a deeper understanding on the crux of the problem concerning the delay and that the public would pay more attention to the happenings in the current system of justice as the repercussions may affect us at one point or another.